Alteration of Hematological and Cardio-Vascular Parameters Among Petrol Filling Workers of West Bengal, India - Majee, Anindita Mandal; Basak, Srijoni (British Journal of Healthcare and Medical Research, 2025)
This study aimed to investigate the effects of volatile organic compounds exposure on blood and cardiovascular parameters of Petrol station workers of West Bengal.The study included 153 male Petrol station workers and 50 male control group individuals of similar socio economic status having age range 20-60 years. Different hematological parameters and cardiovascular parameters (blood pressure and heart rate) has been evaluated. Blood samples were collected and analyzed by fully automated hematology analyzer. The analysis of the results showed significant hematological changes in exposed workers and 21% workers were anaemic. There is a significant decline in hemoglobin and RBC count but significantly higher neutrophil, ESR and eosinophil count were observed compared to the control group. Besides, significantly higher heart rate, systolic and diastolic blood pressure was found in exposed group indicating cardiovascular risk, reflected as hypertension (41.17%). Again, hemoglobin, Red Blood Cell, White Blood Cell and platelet count declined insignificantly and eosinophil count increased significantly with increase in exposure duration. ESR and Neutrophil-Lymphocyte ratio(NLR) values increased maximum above 20 years and between 11-20 years of exposure respectively. This high NLR value is associated with anaemia and hypertension among petrol filling workers. Thus NLR value can be used in routine clinical assessment of anaemia and hypertension. Thus health of workers of fuel station should be protected from exposure to benzene and other toxic substances by introduction of petrol vapour recovery system and minimizing leakage and spillage, by wearing protective gadgets and by giving health education and awareness to these workers.